Determination of Oral Antidiabetic Medications for Type 2 Diabetes Mellitus Patients at Outpatient Department, India - Alam, Md. Shamshir; Maity , Manish Kumar (New Horizons in Medicine and Medical Research Vol. 4, 2022)
Objectives: The study was conducted to determine prescription patterns for oral hypoglycemic agents in type 2 diabetes patients at a university hospital, as well as to evaluate patient compliance with the prescribed therapy. Methods: At a university hospital in New Delhi, India, a prospective, observational, and non-comparative study was conducted over a period of six months. A total of 200 registered type 2 diabetes patients were included in this study. The prescriptions were assessed after the physician's consultation, and the patients were interviewed. A custom-designed proforma was used to collect the data. Key findings: In a group of 200 type 2 diabetics, females made up more than half (53%). The patients' average age and body mass index were 50.4 ± 11.7 years and 25.8 ± 4.4 kg/m2, respectively. The patients were prescribed a total of 432 OHAs. Combination therapy was prescribed to a significantly higher number of patients (71.5%), with a p-value of 0.0001. The most preferred class was biguanides, followed by sulfonylureas, thiazolidinediones and \(α\) glucosidase inhibitors. Only 77.5% of the patients showed good compliance with the regimen. Metformin was documented to be the most often prescribed medicine. Conclusions: The most frequently prescribed OHAs class was biguanides, followed by sulfonylureas, thiazolidinediones, and \(α\) glucosidase inhibitors. Metformin was discovered to be the most often advised medicine.